Urge different campus departments to prepare staff members for crises. Issue 1 (May 2015) - Hope, Joan
<x xml:space="preserve">Abstract</x> Your campus safety unit probably maintains a comprehensive campus emergency plan. It's also a good idea to encourage officials of departments throughout campus to plan ahead so they aren't caught unprepared during emergencies. After all, your overall plan is unlikely to address all the little details that will impact every single campus department, such as the loss of departmental data and health or medical issues of individual employees.